The importance of monitoring the level of ionized magnesium fraction in the blood in critically ill patients - Stanojević, Marija (Journal of Medical Biochemistry, 2025)
Background: Critical illnesses imply dysfunctions of vital organs with high risk of imminent death. Magnesium is a bioessential mineral with multiple physiological effects relevant for vital body functions. It stabilizes excitable membranes contributing to proper neuromuscular, cardiovascular and respiratory functions. Ionized Mg2+ (iMg2+) is free bioactive form of Mg2+ in body fluids. Disorders of Mg2+ status in critically ill and injured patients are often overlooked. Chronic Mg2+ deficiency is a condition of growing incidence in the general population. It is a significant factor in overall morbidity and mortality of the critically ill. Methods: Electronic search was conducted across PubMed library database without time restrictions (up to November 8, 2024), using keywords »ionized magnesium« AND »critical care patients« to identify studies investigating the value of measuring blood concentration of ionized Mg2+ fraction in patients with critical health conditions. Selection criteria included only studies on human, and excluded studies on veterinary population. Results: Since Mg2+ is predominantly an intracellular cation, it is dificult to determine Mg2+ deficiency in the body. Its early stages refer to a clinically unmanifested tissue Mg2+ deficit in the presence of normal ionized and total magnesaemia. Disconcordance between total Mg2+ and iMg2+ blood levels is frequently present in critically ill patients. Concentration of iMg2+ fraction is a more specific marker of general Mg2+ status than total Mg2+. Appropriate electrolyte analyser iMg2+ assay is needed to adequately and promptly determine Mg2+ status, and estimate the requirement for Mg2+ recompense in the case of deficiency. Conclusions: Abnormalities of Mg2+ levels are prevalent in critical patients. Their severity can impose vital threat. Monitoring iMg2+ level to assess Mg2+ status helps diagnose and correct Mg2+ disbalances to provide better patient outcome.